A case of early-stage epithelial ovarian cancer in pregnancy. Issue 5 (1st September 2001) - Otton, G.; Higgins, S.; Phillips, K. A.; Quinn, M.
Abstract : There are few reports in the literature of platinum-based chemotherapy administered in pregnancy. We present a case of serous adenocarcinoma of the ovary complicating pregnancy. Following laparotomy at 16 weeks of gestation, four cycles of cisplatin were administered prior to confinement at 32 weeks. There were no neonatal sequelae. We believe there is increasing evidence for the safe use of cisplatin in pregnancy.